Microstructural effects on the wetting-induced collapse in compacted loess. (October 2021) - Ge, Miaomiao; Pineda, Jubert A.; Sheng, Daichao; Burton, Glen J.; Li, Ning
Abstract: This paper presents the results of an experimental study aimed at evaluating the effects of soil microstructure on volume change and wetting-induced collapse of a compacted loess from Xi'an, China. One-dimensional (1D) compression tests are combined with Mercury Intrusion Porosimetry (MIP) tests and Scanning Electron Microscopy (SEM) analysis to examine the collapse behaviour for different compaction states and applied stresses. A phenomenon of partial collapse occurs upon full saturation (wetting), whose magnitude depends on the as-compacted suction, the as-compacted microstructure and the stress level applied. Following partial collapse upon full saturation some of the initially meta -stable microstructure of the compacted soil is preserved which leads to higher compressibility in subsequent loading stages. Additional collapse tests carried out under isotropic conditions show that partial collapse upon full saturation takes place only under zero-lateral deformation (1D) conditions due to the residual ('locked-in') horizontal stresses maintained in the sample after compaction. Microstructural results and a simple macroscopic model for soil compaction are used to qualitatively explain the phenomenon of partial collapse observed in compacted loess.